Protective effect of Limosilactobacillus fermentum HFY06 on dextran sulfate sodium-induced colitis in mice - Liu, Bihui; Yang, Lei; Wu, Ya; Zhao, Xin (Frontiers in Microbiology, 2022)
Ulcerative colitis is one of the main gastrointestinal diseases that threaten human health. This study was investigated the effect of Lactobacillus fermentum HFY06 (LF-HFY06) on dextran sulfate sodium (DSS)-induced murine colitis. The experimental strain (LF-HFY06) was isolated from fermented yak yogurt. The protective effect of LF-HFY06 was evaluated by examining the length and histopathological sections of colon, related biochemical indicators, and related genes. Direct and microscopic observations showed that LF-HFY06 increased the length of the colon and ameliorated the pathological damage induced by DSS. The biochemical indicators showed that LF-HFY06 enhanced the activities of antioxidant enzymes total superoxide dismutase (T-SOD) and catalase (CAT) in serum, while reducing the level of malondialdehyde (MDA). It was also observed that the serum inflammatory cytokines levels of tumor necrosis factor-α (TNF-α), interferon (IFN)-γ, interleukin (IL)-1β, IL-6, and IL-12 were decreased, and the anti-inflammatory cytokine IL-10 level was increased. The q-PCR experiment revealed that LF-HFY06 downregulated the mRNA expression levels of nuclear factor-κB-p65 (NF-κBp65), TNF-α, IL-1β, IL-6, and cyclooxygenase 2 (COX-2) in colon tissues, and upregulated the mRNA expression of NF-κB inhibitor-α (IκB-α) and IL-10. These data indicated that LF-HFY06 inhibited inflammation through the NF-κB signaling pathway to prevent the occurrence and development of colitis. This research demonstrates that probiotics LF-HFY06 has the potential to prevent and treat colitis.